Making a living in Ottoman Anatolia (Leiden ; Boston)
xii, 265 sayfa
Keywords: “Centred on the socio-economic life of Ottoman Anatolia, this volume examines aspects of production, local and international trade, consumption and the role of the state, both at a local and a central level. Based on a wide array of data and adopting a variety of approaches, chapters range from the macro to the micro, from the overview of Anatolian economic resources to the in-depth examination of the petition language of provincial economic actors. Making a Living in Ottoman Anatolia thus offers the reader an entrée into the rich and varied socio-economic life of a central region of the Ottoman empire. Contributors are Marc Aymes, Ebru Boyar, Metin Coşgel, Suraiya Faroqhi, Kate Fleet, Elena Frangakis-Syrett, Yonca Köksal, Mehmet Öz, Mehmet Polatel and Sadullah Yıldırım“ --